Academic Burnout of Students Working in Metropolitan Cities: RASCH Model Analysis - Hayu Stevani; Maria Oktasari; Herul Wahyudin; Rizky Andana Pohan; Cici Yulia (Jurnal Keilmuan Pendidikan, 2025)
During the Covid-19 pandemic, all aspects of public life were restricted, including online learning. In the process of online learning, the high number of academic targets that had to be achieved led to burnout. This study identifies academic burnout among working students in Jakarta, Indonesia. The data used were part of a pilot study conducted by the authors to assess students' academic burnout. This research employed a survey method with Rasch model analysis, using a sample of 451 participants who completed the survey via Google Form distributed through WhatsApp messages. The instrument used was the School Burnout Inventory (SBI) (Salmela et al., 2009). The results showed that 17% of students fell into the low academic burnout category, while the remaining were in the medium (59%) and high (24%) categories. Therefore, it can be concluded that working students experience academic burnout, and counseling is needed to help reduce academic burnout among students working in metropolitan areas.